Does poverty cause dental caries?. (16th December 2018) - Foley, M; Akers, HF
Abstract: Dental caries generates significant health, financial and social costs to individuals and communities, but risk factors are not spread randomly and evenly throughout populations. People from lower socio‐economic status (SES) and disadvantaged groups suffer a disproportionately greater disease burden. Clinicians and public health experts view this problem through a different lens. Dentists at the clinical coalface consider individual risk factors and behaviours, for example sugar consumption, cariogenic bacteria and poor oral hygiene, as major causes of dental caries. However, considerable evidence suggests that low SES, via traditional individual risk factors as mediators and through additional independent pathways, is another significant cause. Progressive clinical practice uses education, prevention and treatment to reduce the impact of individual risk factors. Policy‐makers and health administrators use population‐based approaches to improve the health of societies. The authors use literature review to argue for both a greater awareness of the upstream socio‐economic causes of dental caries, and action from key community sectors to redress the societal inequalities contributing to dental health inequalities.